FAR out? An examination of converging, diverging and intersecting smart grid futures in the United Kingdom - Balta-Ozkan, Nazmiye; Watson, Tom; Connor, Peter M.; Axon, Colin J.; Whitmarsh, Lorraine; Spence, Alexa; Baker, Philip E. (Elsevier, 2020)
We describe a novel application of the field anomaly relaxation (FAR) method of scenario construction to the complex problem of smart grid development. We augment the FAR methodology with extensive expert input through all four steps to incorporate detailed knowledge of the technical, economic and policy issues relevant to informing scenarios for smart grid development in the United Kingdom. These steps inform scenarios useful to policymakers, regulators and the energy industry. We found this extended method to be flexible and reliable. Analysis of smart grid development yielded seven dimensions, allowing for portrayal of a complex and informed set of scenarios. The expert input and feedback identified branching points allowing switching between scenarios – a powerful dynamic feature to assist policy development for a fast-changing technological and regulatory landscape.
Keywords: Participatory scenario; FAR method; Smart grid scenario; Energy scenario; Scenario development; Field anomaly relaxation